Discovery layer decisions, configurations and strategies - R. Schwartz (Библиосфера, 2020)
The problem that patrons frequently encounter with searching via a discovery layer linked to a knowledgebase is the overwhelming number of hits. Few if any research or discussion compares how libraries resolve this difficulty. To begin a discussion, the author disseminated an open invitation for academic libraries to participate on three panels from October 2018 to June 2019 to discuss their implementation processes and decisions. Five academic libraries accepted the invitation. This paper reviews the approaches of the five American academic library systems with the intent to encourage further examination of the issues of design, implementation, and maintenance of discovery layers. The conclusions reached point to the evolving nature of discovery layer interfaces and the struggle for libraries to adapt their needs to this still changing product type. Within this group, the larger institutions with more financial and staff resources have designed a ‘’bento box’’ interface with open source software, while the other institutions with lesser means have chosen to create different instances of their subscribed proprietary discovery layers to meet their specific institutional demands and the specific needs of their patrons. A statistically relevant examination with rigorous comparison of usability testing would have to be done to see how these and other factors play out in the wider field.